2004
DOI: 10.1115/1.1777586
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gravity, Shear and Surface Tension in Internal Condensing Flows: Results From Direct Computational Simulations

Abstract: The paper presents accurate numerical solutions of the full two-dimensional governing equations for steady and unsteady laminar/laminar internal condensing flows. The results relate to issues of better design and integration of condenser-sections in thermal management systems (looped heat pipes, etc.). The flow geometry, in normal or zero gravity, is chosen to be the inside of a channel with film condensation on one of the walls. In normal gravity, film condensation is on the bottom wall of a tilted (from vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
76
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(93 citation statements)
references
References 16 publications
16
76
1
Order By: Relevance
“…The numerical scheme used here exploits the rigorous analytical and numerical knowledge that exists (see [19]) for solving a reduced hyperbolic form of the interface tracking equation-this ensures convergence and accuracy of both the amplitude and the phase of the predicted interfacial waves. Due to an algorithm improvement, the convergence, grid independence, and satisfaction of all interface/boundary conditions for the results reported here are better than what were reported in [1,2].…”
Section: Introductioncontrasting
confidence: 61%
See 3 more Smart Citations
“…The numerical scheme used here exploits the rigorous analytical and numerical knowledge that exists (see [19]) for solving a reduced hyperbolic form of the interface tracking equation-this ensures convergence and accuracy of both the amplitude and the phase of the predicted interfacial waves. Due to an algorithm improvement, the convergence, grid independence, and satisfaction of all interface/boundary conditions for the results reported here are better than what were reported in [1,2].…”
Section: Introductioncontrasting
confidence: 61%
“…The in-tube geometry (see Fig. 1a) is considered here while some new and improved results for the horizontal and zero gravity channel flow cases-formulated elsewhere [1,2]-are also presented. The results are important for a qualitative understanding of experiments (see, e.g., [3]) dealing with the behavior of a condenser-section (typically of hydraulic diameters in millimeter or sub-millimeter range).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that the elliptical section tube has a clear improvement of the vapor condensation over horizontal cylinder. Recently, the stability of the condensing flows has been discussed numerically and experimentally in several works [23][24][25][26][27]. The effect of the free-stream vapor-striking angle on the condensation over a vertical plate was analyzed by Khaled et al [28].…”
Section: Introductionmentioning
confidence: 98%